1990
DOI: 10.1002/jlac.199019900189
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal‐ and acid‐induced transformations of 6‐siloxy‐substituted 5,6‐dihydro‐4H‐1,2‐oxazines: Preparation of pyrroles, nitrones, 1,4‐dicarbonyl compounds and derivatives thereof

Abstract: A variety of 6‐siloxy‐substituted 5,6‐dihydro‐4H‐1,2‐oxazines (abbreviation: 1,2‐oxazines) 1, 3 could be transformed into di‐ and trisubstituted pyrroles 2, 4 by means of molybdenum hexacarbonyl. The mechanism of this deoxygenating ring contraction is discussed. With two bicyclic 1,2‐oxazines an acid‐catalyzed fragmentation affording α‐methylenecycloalkanones 7 has been observed, while other 1,2‐oxazines rearrange in methanolic acid to give nitrones 9, 10. The desilylation of 6‐siloxy‐substituted 1,2‐oxazines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Pyrroles can be synthesized from dihydrooxazines 145 containing a heteroatomic substituent at C-6, for example, when X is an alkoxy, siloxy, or amino group (Scheme ). Nakanishi , and Reissig , showed that dihydrooxazines 145 are smoothly transformed into pyrroles 146 upon the action of metal carbonyls [Mo(CO) 6 , Fe(CO) 5 , Fe 2 (CO) 9 , and Fe 3 (CO) 12 ] (Scheme ). The best yields are obtained when Mo(CO) 6 or Fe 3 (CO) 12 in the presence of trifluoroacetic acid is employed.…”
Section: Chemical Properties Of Scoementioning
confidence: 99%
See 4 more Smart Citations
“…Pyrroles can be synthesized from dihydrooxazines 145 containing a heteroatomic substituent at C-6, for example, when X is an alkoxy, siloxy, or amino group (Scheme ). Nakanishi , and Reissig , showed that dihydrooxazines 145 are smoothly transformed into pyrroles 146 upon the action of metal carbonyls [Mo(CO) 6 , Fe(CO) 5 , Fe 2 (CO) 9 , and Fe 3 (CO) 12 ] (Scheme ). The best yields are obtained when Mo(CO) 6 or Fe 3 (CO) 12 in the presence of trifluoroacetic acid is employed.…”
Section: Chemical Properties Of Scoementioning
confidence: 99%
“…The intermediate 147 is suggested to result from the elimination of HX molecule from the starting dihydrooxazine 145 . The second variant postulates the initial cleavage of the weak N−O bond in oxazine 145 with carbonyl M(CO) n to form complex 149 . The latter decomposes upon the action of acid HX, giving aldimine 150 , which further is cyclized to the final pyrrole 146 .…”
Section: Chemical Properties Of Scoementioning
confidence: 99%
See 3 more Smart Citations